PENGUATAN KOPERASI WANITA MELALUI PENINGKATAN SISA HASIL USAHA KOPERASI - Sriyono Sriyono; Suci Anggrainy Setyowati (FE Program Studi Manajemen, 2022)
This study aims to determine the effect of Own Capital, Loan Capital, Business Volume, Total Assets, Number Of Member and Receivables Against Remaining Operations (SHU) in Women Cooperatives in Sidoarjo City. The improvement of the remaining business outcomes for cooperatives is very important to do because it relates to welfare for its members. Not many studies have been conducted by preliminary researchers on the strengthening of the rest of the business results.The data analysis uses secondary data. The population in this study is the financial statements of womens cooperative registered at the Sidoarjo Regency cooperative period 2013-2017. Based on the application of purposive sampling method, 43 womens cooperative were obtained as samples. The result was obtained based on Multiple Regression with partial and simultaneous tests results obtained are Own Capital, Loan Capital, Business Volume, Total Assets, Number of Member and Receivable Significant effect on SHU.